Joseph Galloway family papers - Galloway, Joseph, 1731-1803.
Chiefly family correspondence of Galloway, his wife, Grace Growden Galloway, their daughter, Elizabeth, and Mrs. Galloway's brother, Thomas Nickelson, of Dorset, England. Includes travel notebook (1770-1808) and letters (1776-1781) of Galloway to his wife; verses written and collected by Grace Galloway, together with letters describing her trials as a Loyalist wife during the American Revolution; and correspondence of Elizabeth with English friends.
Loyalist and member of the Continental Congress and Pennsylvania Assembly.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Collection material in English.
Keywords: Galloway, Elizabeth, -- approximately 1754- -- Correspondence; Galloway, Grace Growden, -- -1789 -- Correspondence; Nickelson, Thomas -- Correspondence; Galloway family; Pennsylvania. -- General Assembly; United States. -- Continental Congress; American loyalists; United States -- History -- Revolution, 1775-1783.; Legislators -- Pennsylvania